The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/smll.200600240
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Particulate Reservoir‐Containing, Capsulelike, and Self‐Folding Polymer Microstructures for Drug Delivery

Abstract: Particulate polymer microdevices are fabricated using protocols based on a transfer‐molding process that allows the controlled assembly of multiple materials to produce functional devices. Specifically, protocols for reservoir‐containing (see image; scale bar=100 μm), capsulelike, and self‐folding polymer microdevices are presented. The encapsulated materials are not exposed to high temperatures or caustic solutions, which is important in drug‐delivery applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 18 publications
0
98
0
4
Order By: Relevance
“…[7][8][9][10] This process has also been used to fabricate multilayer microscale polymeric vesicles for drug delivery. 11,12 Here, we employ scrolling in the fabrication of adaptable polymer particles that can alter their geometry when triggered by given stimuli, such as temperature, thus altering flow characteristics and adsorption properties, provide understanding of how the materials and processing conditions alter the particle geometry, and quantify the responsive kinetics for these particles.…”
mentioning
confidence: 99%
“…[7][8][9][10] This process has also been used to fabricate multilayer microscale polymeric vesicles for drug delivery. 11,12 Here, we employ scrolling in the fabrication of adaptable polymer particles that can alter their geometry when triggered by given stimuli, such as temperature, thus altering flow characteristics and adsorption properties, provide understanding of how the materials and processing conditions alter the particle geometry, and quantify the responsive kinetics for these particles.…”
mentioning
confidence: 99%
“…The materials such as poly(ethyl glycol) dimethycrylate (PEGDMA) is used for such process. Such photolithography also includes exposing the substrate to the UV light which results in filling of microdevices with drugs for sequential delivery of therapeutics [30]. Besides, these micro-reservoirs can also be filled with drugs using microinjection techniques.…”
Section: A Micropatchmentioning
confidence: 99%
“…While SU-8 is not currently FDA approved, studies have shown that SU-8 is non-toxic as an implantable material [5355]. Other biocompatible polymers utilized for microdevice fabrication include chitosan [56], gelatin [57], poly(lactic-co-glycolic) acid (PLGA) [5658], polypropylene (PP) [59], and poly(ethylene glycol) (PEG) [27, 52, 56]. The intrinsic biocompatibility, biodegradation, hydrophobicity, and structural properties of individual polymers can be tuned by adjusting the chemical structure of the monomer(s) used in polymer synthesis, the molecular weight of the polymer, and/or the crosslinking density [56, 6062].…”
Section: Materials Utilized For Microdevice Structurementioning
confidence: 99%
“…These patterned elastomers can be used as either a mold, to create devices from recessed regions, or as a stamp, which can be coated with material to create devices or patterned surface modifications in regions of contact. Guan et al have demonstrated a variety of soft lithography techniques that can be utilized to fabricate microdevices (Figure 3) [56, 5960, 68]. In one study, a micropillar PDMS stamp was coated with PPMA before bringing the stamp into contact with a glass slide coated with polyvinyl alcohol (PVA), creating PPMA microdevices in regions of contact (Figure 3A) [59].…”
Section: Techniques Utilized In the Micro- And Nanofabrication Of Oramentioning
confidence: 99%